PERAN KEPEMIMPINAN KEPALA SEKOLAH DALAM PENINGKATAN MANAJEMEN MUTU PENDIDIKAN - Rahmadhani, descha rahmadhani; Aprilyana Cengkas , Lily; Dewi, Sulfiana; Fitriani; Dwiyono, Yudo (SISTEMA: Jurnal Pendidikan, 2023)
The quality of education is a big challenge in the education sector in Indonesia, both at the higher education level and primary and secondary schools. The leadership of the school principal is important in improving the quality of educational management. The aim of this research is to find out how the leadership role of school principals can improve the management of educational quality. The research method used is a quantitative approach and data collection through library research. The findings in this research indicate that the way school leaders act professionally has both positive and negative impacts on teachers, counselors and other academic staff. This study also shows that the quality of education is closely related to the leadership responsibilities of school principals and the administrative organization, which is responsive to the educational needs of regional and municipal councils. To improve the quality of education, school leaders must focus on the small things, because these things are often overlooked, even though they have a big impact on progress. Keywords: Leadership, Total Quality Management